Prevalence, serotypes and virulence genes of streptococcus agalactiae isolated from pregnant women with 35–37 weeks of gestation - Bobadilla, Fernando Javier (2021)
Fil: Bobadilla, Fernando Javier. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina.